“THE ANIMALS ARE DYING. SOON WE WILL BE ALONE HERE”: ANTHROPOCENE, CAPITALOCENE, AND THE NEW DYSTOPIAN TRENDS FROM THE GLOBAL SOUTH - Marks de Marques, Eduardo (Abusões, 2024)
The current climatic and environmental changes have been bringing about a number of new anxieties, mostly consolidated in concepts such as the Anthropocene and the Capitalocene, which can be seen as partially responsible for the rise in interest in dystopian fiction since the early years of the 21 st century. However, a possible new trend is found in contemporary dystopian fiction from the Global South, inviting a reassessment of the very foundations of what we understand this trope to be. The present article wishes to discuss some of these trends using the novel Migrations (2022), by Charlotte McConaghy, as an example.